Integrating intravenous frusemide treatment into the community for heart failure patients. (25th November 2020) - Caples, N; Gorry, C; Hennessy, A; Regan, A; Burke, M; Collier, D; Asgedom, S; Owens, P
Abstract: Background: A structured pathway was developed to allow patients to safely receive intravenous (i/v) frusemide at home. This pathway was implemented by an integrated team consisting of primary and tertiary care. This allowed the traditional acute hospital treatment to be now delivered in the community. Purpose: This concept has been used on an individual case basis by a minority of acute hospitals. Previously there was no structured pathway that would allow this treatment to become a standard part of heart failure treatment by acute hospitals. The pathway would ensure that the treatment would be delivered safely to a cohort of patients who meet certain criteria. Methods: A pathway was developed by a consultant cardiologist, heart failure (HF) nurses and the Community Intervention Team (CIT)/CareDoc. The Caredoc Community Intervention Team (CIT) is a nurse led professional team that provides acute nursing care to patients in the community setting. The HF nurse would identify the suitable patient for i/v frusemide as per pathway. A referral would be sent to the CIT team who would administer the frusemide at the patients home. The CIT team would take a renal profile daily, check vital signs, check symptoms of HF and check daily weight on the patient while they were receiving i/v frusemide. The bloods results would be reviewed daily by the HF nurse. The HF nurse would liaise daily with the CIT team and patient for symptoms, daily weights and vital signs. The patient would then be reviewed in the HF clinic post treatment. Results: Single centre retrospective analysis was undertaken of the patients who received i/v frusemide at home over a 3 year period. 83 patients meet the inclusion criteria and received the treatment. 70 male and 13 female. Average age 78 years old. Average length of treatment 3 days. Treatment was given twice daily, average daily dose was 137 mg. Majority of treatment was 80mg bd or 60 mg bd. No failure cannulating any patient as CIT had high cannulation skills due to regular cannulation as part of workload. 3 episodes of hypokalaemia, lowest potassium was 3.1 mmols, all 3 episodes were effectively treated with oral potassium supplements. No significant acute kidney injury was noted that required change to treatment. 6 patients required heart failure associated admission to hospital, 3 had hypotension, 1 has fast A-flutter and 2 remained resistance to i/v frusemide and required inotropes. Both patient and carers reported a high satisfaction rate with the service. Conclusion: National length of stay for a HF patient in Ireland is 11 days.This novel structured pathway successfully selected appropriate patients who can safely receive i/v frusemide at home. 93% avoided hospital admission.This reduces the need for acute hospital admission and significant associated costs. Patients and carers rated 95% satisfaction with service.Sustainability of the project is driven by an integration team approach. Funding Acknowledgement: Type of funding source: None